PENGARUH KOMPENSASI, MOTIVASI, KOMITMEN ORGANISASIONAL DAN PENGETAHUAN AKUNTANSI TERHADAP KINERJA KARYAWAN BAGIAN AKUNTANSI (Survei pada Koperasi Karyawan Perusahaan Manufaktur di Kabupaten Pati) - Monica Zelvia Conny Astari, Rispantyo & Djoko Kristianto (Universitas Slamet Riyadi, 2017)
The performance of Accountants in conducting its work is influenced byvarious factors, such as compensation, motivation, organizational commitment andknowledge of accounting. The purpose of this study was to analyze the effect betweencompensation, motivation, organizational commitment and knowledge of accountingor partially simultaneously against the performance of an employee the accountingsection. This study used a case study on the employee's part in cooperativeaccounting Manufacturing Company Employee Pati. The data type used isqualitative data and quantitative data, the source data used the primary data.Populations and samples in this study are all employees of the accounting section atCoop Employees manufacturing company in Pati as much as 32 employees, so thisresearch is the study of the census. Technique of data analysis used a classicassumption test, and multiple linear regression analysis. The research resultsobtained a conclusion that compensation, motivation, organizational commitmentand knowledge of accounting are partial and significant effect simultaneously onperformance of employees accounting section on Employee Cooperativemanufacturing company in Pati.Keywords: motivation, compensation, organizational commitment, knowledge ofaccounting, accounting employee performance.